Práticas de leitura e escrita em contexto acadêmico: relações (hiper)textuais singulares - Komesu, Fabiana Cristina [UNESP]; Galli, Fernanda Correa Silveira [UNESP] (My University, 2014)
The present article aims at reflecting about the discursive practices of writing and reading on the net, more specifically about the writing and reading methods used by the undergraduate and graduated teachers, based on an internet search engine. It’s of interest to investigate: i) the (hyper) textual relations established in the context thought as permitted by the electronic resources; ii) the discursive marks that arise (are arisen) in a singular way of reading (and/or writing). The set of material was produced during a university extension course about reading and cyberspace, whose context consisted of a drawing production of the reading process on an internet search engine, on the basis of the signifier “apple”. Based on the French Discourse Analysis and assumptions from the New Literacy Studies, we intended to discuss the operating procedures of the internet search and the effects of meanings produced by the subject during his/her reading/writing process.

No presente artigo, temos como objetivo refletir sobre as práticas discursivas de leitura e de escrita em/na rede, mais especificamente, sobre os percursos de leitura/escrita realizados por professores em formação e já formados, com base num motor de busca da internet. Interessa-nos, de maneira particularizada, investigar: i) as relações (hiper)textuais estabelecidas no enredamento entendido como viabilizado por recursos eletrônicos; ii) as marcas discursivas que (se) fazem emergir (n)um modo singular de ler (e de escrever). O conjunto do material foi produzido num curso de extensão universitário sobre leitura e ciberespaço, cuja proposta consistia na produção de um desenho do percurso de leitura num motor de busca da internet, a partir do significante “maçã”. Inscritas no referencial teórico da Análise do Discurso francesa e em pressupostos advindos dos Novos Estudos de Letramento (New Literacy Studies), procuramos discutir o funcionamento de mecanismos de busca da internet e os efeitos de sentidos produzidos pelo sujeito em seu trajeto de leitura/escrita.
Writing and reading practices in an academic context (hyper) textual singular relations
Keywords: Letramento Acadêmico; Leitura; Escrita; (Hiper)texto; Rede; Academic Literacy; Reading; Writing; (Hyper)Text; Net